Structure, Biology, and Therapeutic Implications of Pegylated Interferon Alpha-2b - Youngster, S.; Wang, Y-S.; Grace, M.; Bausch, J.; Bordens, R.; Wyss, D.F. (Current Pharmaceutical Design, 2002)
Derivatization of protein-based therapeutics with polyethylene glycol (pegylation) can often improve pharmacokinetic and pharmacodynamic properties of the proteins and thereby, improve efficacy and minimize dosing frequency. This review will provide an overview of pegylation technology and pegylated protein-based drugs being used or investigated clinically. The novel therapeutic, PEG Intron, formed by attaching a 12-kDa mono-methoxy polyethylene glycol (PEG) to the interferon alpha-2b protein, will be discussed in detail in terms of its structure, biological activities, pharmacokinetic properties, and clinical efficacy for the treatment of chronic hepatitis C. Detailed physicochemical and biological characterization studies of PEG Intron revealed its composition of pegylated positional isomers and the specific anti-viral activity associated with each of them. Pegylation of Intron A at pH 6.5 results in a mixture of ≥ 95% mono-pegylated isoforms with the predominant species (approximately 50%) derivatized to the His34 residue with the remaining positional isomers pegylated at various lysines, the N-terminal cysteine, as well as serine, tyrosine, and another histidine residue. The anti-viral activity for each pegylated isomer showed that the highest specific activity (37%) was associated with the His34-pegylated isomer. Though pegylation decreases the specific activity of the interferon alpha-2b protein in vitro, the potency of PEG Intron was comparable to the Intron A standard at both the molecular and cellular level. The substituted IFN had an enhanced pharmacokinetic profile in both animal and human studies, and, when combined with ribavirin, was very effective in reducing hepatitis C viral load and maintaining sustained viral suppression in patients.
Keywords: hepatitic c